2021
DOI: 10.37349/ei.2021.00018
|View full text |Cite
|
Sign up to set email alerts
|

The two faces of mast cells in vitiligo pathogenesis

Abstract: Aim: Previously, we reported increased number of T helper 17 (Th17) cells in vitiligo. However, in our recent study, tryptase and interleukin (IL)17 double positive cells which identified by polyclonal anti-IL17 antibody with specificity for IL17A, B, D, F was observed, but these mast cells cannot be stained by monoclonal anti-IL17 antibody with specificity for IL17A. Therefore, this study was aimed to clarify the role of mast cells in induction and progression of vitiligo. Methods: Mast cells were stained wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In addition, IL-4, IL-13, and IL-33 levels are increased in the serum of vitiligo patients ( 126 129 ). An increase in mast cells in vitiligo lesions was reported ( 130 , 131 ). Czarnowocki et al.…”
Section: Vitiligomentioning
confidence: 97%
“…In addition, IL-4, IL-13, and IL-33 levels are increased in the serum of vitiligo patients ( 126 129 ). An increase in mast cells in vitiligo lesions was reported ( 130 , 131 ). Czarnowocki et al.…”
Section: Vitiligomentioning
confidence: 97%
“…The IFN-γ-chemokine signalling axis is responsible for autoreactive CD8 T cell recruitment and localisation as well as their effector function in the inflamed site through a positive feedback loop [ 181 ]. The role of MCs in vitiligo pathogenesis might be both positive and negative [ 182 ]. Histopathological studies have revealed an increased number of MCs as well as their degranulation in the lesional dermis of vitiligo [ 182 ].…”
Section: Modalities Of Mast Cell–cd8 T Cell Interactions In the Skin:...mentioning
confidence: 99%
“…The role of MCs in vitiligo pathogenesis might be both positive and negative [ 182 ]. Histopathological studies have revealed an increased number of MCs as well as their degranulation in the lesional dermis of vitiligo [ 182 ]. In an in vitro culture system, MC-derived histamine stimulates melanogenesis via histamine H2 receptors in melanocytes through a process involving protein kinase A activation and induces persistent hyper-melanosis in response to the excessive expression of paracrine factors (e.g., SCF) by epidermal keratinocytes [ 183 , 184 ].…”
Section: Modalities Of Mast Cell–cd8 T Cell Interactions In the Skin:...mentioning
confidence: 99%